Factors in Improving Financial Management Practices for Sustainable Growth of Micro, Small and Medium Enterprises in Ethiopia - Zemo, Gebreamlak Yitbarek; Vértesy, László (Acta Carolus Robertus, 2025)
This study seeks to investigate how the practices of financial management improve the sustainable growth of micro, small, and medium enterprises (MSMEs) in Ethiopia. The study adopts a mixed-method approach, combining quantitative and qualitative research designs to gather and analyze the data. It focuses on MSMEs in three sub-cities of the capital, selecting a sample of 337 MSMEs using simple random and stratified sampling methods. The study used interviews and questionnaires to collect the data, examining key financial management aspects such as cash flow management practices, investment decision-making practices, and financial analysis and reporting, and inventory management practices. Both primary and secondary data were analyzed through inferential statistical and descriptive methods. The results indicate a significant positive relationship between financial management practices and the sustainable growth of MSME entrepreneurs. However, several critical challenges hinder MSME success, including inadequate record-keeping, limited financial literacy among managers and owners, and inefficient inventory and cash flow management practices. Furthermore, many business owners fail to leverage modern financial tools for informed investment decision-making. To enhance MSMEs’ business understanding and skills of, the government should offer financial training programs, advisory services, mentorship and coaching opportunities, facilitate access to financing, and implement monitoring and evaluation systems. These initiatives can significantly contribute to their sustainable growth.